Current state of hypnotic use disorders: Results of a survey using the Japanese version of Benzodiazepine Dependence Self‐Report Questionnaire. Issue 1 (1st December 2020) - Yamamoto, Mai; Inada, Ken; Enomoto, Minori; Habukawa, Mitsunari; Hirose, Takahisa; Inoue, Yuichi; Ishigooka, Jun; Kamei, Yuichi; Kitajima, Tsuyoshi; Miyamoto, Masayuki; Shinno, Hideto; Nishimura, Katsuji; et al.
Abstract: Aims: Benzodiazepine receptor agonists (BZ‐RAs) are frequently prescribed to treat insomnia; however, their long‐term use is not recommended. To introduce an appropriate pharmaco‐therapy, the current state and background factors of BZ‐RAs' dependence must be elucidated. In this study, we developed a Japanese version of the Benzodiazepine Dependence Self‐Report Questionnaire (Bendep‐SRQ‐J) and conducted a study of BZ‐RAs' use disorder. Methods: The Bendep‐SRQ‐J was created with permission from the original developer. Subjects were inpatients and outpatients receiving BZ‐RAs between 2012 and 2013. Clinical data collected were Bendep‐SRQ‐J scores, sleep disorders for which BZ‐RAs were prescribed, physical comorbidities, psychotropic drugs, and lifestyle factors. Logistic analysis was performed to extract factors associated with severe symptoms. Results: Of the 707 patients prescribed BZ‐RAs, 324 had voluntarily tapered or discontinued their drugs. Logistic analysis showed that the total number of drugs administered in the last 6 months correlated with both worsening of symptoms or conditions. This was more notable among younger patients, and the proportion of patients with severe symptoms or conditions increased with the increasing number of drugs. Conclusion: Using the Bendep‐SRQ‐J, we elucidated the current state of BZ‐RA dependence. Nearly half of the patients were non‐compliant. The proportion of patients with severe symptoms or disease conditions increased with the increase in the number of drugs administered. These findings highlight the need for clinicians to be aware of the likelihood of benzodiazepine dependence, especially in young patients and patients prescribed multiple hypnotics. Abstract : Using the Bendep‐SRQ‐J, we elucidated the current state of BZ‐RA dependence. Nearly half of the patients were non‐compliant.